Relapse of Evaluative Learning-Evidence for Reinstatement, Renewal, but Not Spontaneous Recovery, of Extinguished Evaluative Learning in a Picture-Picture Evaluative Conditioning Paradigm - Luck, Camilla; Lipp, Ottmar (2019)
In evaluative conditioning, if one shape (conditional stimulus [CS]; CSp) is paired with pleasant unconditional stimulus (US) images and another (CSu) is paired with unpleasant US images differential CS valence and US expectancy develops, such that participants evaluate the CSp as more pleasant and more predictive of pleasant images than the CSu. This conditional CS valence and US expectancy can be reduced in an extinction procedure in which the CSs are repeatedly presented alone. We investigated whether evaluative and expectancy learning is subject to relapse (spontaneous recovery, reinstatement, and renewal) after extinction in a picture-picture evaluative conditioning paradigm. In Stream 1, after acquisition and extinction, the spontaneous recovery test was completed after a delay. During the spontaneous recovery test, conditional expectancy learning, but not conditional evaluative learning, returned. In Stream 2, the US pictures were presented in a random stream after extinction (reinstatement manipulation) which led to the return of conditional evaluative and expectancy learning. In Stream 3, after acquisition training in Context A and extinction training in Context B, conditional expectancy and evaluative learning returned when participants completed the renewal test in the acquisition context (Context A; ABA renewal). Overall, the results suggest that conditional evaluative learning is subject to reinstatement and renewal, but not to spontaneous recovery, in a picture-picture evaluative conditioning paradigm.